Economics : the user's guide - Chang, Ha-Joon (Bloomsbury Press, 2014)
"Unlike many economists, who present only one view of their discipline, Chang introduces a wide range of economic theories--from the Classical economists to the Behavioral economists, from the Marxists to the Austrians--revealing how each has its strengths and weaknesses and why there is no one correct way to explain economic behavior. Instead, by challenging received wisdom and exposing the myriad institutional, political, and technological forces that shape our economic world, Chang explains how our increasingly global and interconnected world works and is evolving. Economics: The User's Guide is a concise and expertly crafted guide to economic theories, and will give all who read it a clear and accurate picture of the global economy and how and why it affects our daily lives."--Jacket.